2022
DOI: 10.1038/s41598-022-18392-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupations and their impact on the spreading of COVID-19 in urban communities

Abstract: The current pandemic has disproportionally affected the workforce. To improve our understanding of the role that occupations play in the transmission of COVID-19, we analyse real-world network data that were collected in Bucharest between August 1st and October 31st 2020. The data record sex, age, and occupation of 6895 patients and the 13,272 people they have interacted with, thus providing a social network from an urban setting through which COVID-19 has spread. Quite remarkably, we find that medical occupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…A recent study reported that medical occupation does not impact the infection spread. Interestingly, females are slightly more likely to test positive than males [ 4 ]. Data on gender for the first 250 days of the COVID-19 pandemic in Bucharest, Romania showed that 53.2% of COVID-19 cases were females, and gender and age data should influence the prevention measures [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that medical occupation does not impact the infection spread. Interestingly, females are slightly more likely to test positive than males [ 4 ]. Data on gender for the first 250 days of the COVID-19 pandemic in Bucharest, Romania showed that 53.2% of COVID-19 cases were females, and gender and age data should influence the prevention measures [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To prevent a high number of morbidities, mortalities, and economic crises during the epidemic, a wide proportion of the population should gain immunity via vaccination, 9 as having been proved in many other infections such as influenza and meningitis, in which mass vaccination played an effective role in obtaining the herd immunity. 10 The rapid progress of multiple vaccines with different platforms resulted in the development of a negative public attitude toward COVID-19 vaccination; however, COVID-19 vaccines have been highly effective in curtailing symptomatic and severe forms of COVID-19 and its associated mortality. 8 Moreover, a modest reduction in vaccine effectiveness was observed against mild disease with some variants; however, its effectiveness against severe forms of disease remained high at least 6 months after immunization with two doses.…”
Section: Introductionmentioning
confidence: 99%
“…Although herd immunity can be achieved when adaptive immunity occurs in a high percentage of the population worldwide. To prevent a high number of morbidities, mortalities, and economic crises during the epidemic, a wide proportion of the population should gain immunity via vaccination, 9 as having been proved in many other infections such as influenza and meningitis, in which mass vaccination played an effective role in obtaining the herd immunity 10 …”
Section: Introductionmentioning
confidence: 99%
“…Limited information is available regarding SARS-CoV-2 infection, immune response and COVID-19 risk in frontline workers at urban medical centers who have among the greatest chance of exposure. Interestingly, Hancean et al found that urban medical occupations do not significantly drive viral transmission as compared to non-medical professions (1). The tendency for individuals to associate with those who are similar to themselves (e.g.…”
Section: Introductionmentioning
confidence: 99%